From RPP to Teaching Modules: Challenges and Practices of ISMUBA Teachers - Rahmalia, Nuriza; Madjid, Abd. (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2026)
The implementation of the Independent Curriculum has brought significant changes in learning planning, particularly in the transition from the 2013 Curriculum Lesson Plan (RPP) to teaching modules. This shift requires teachers to adapt to new principles such as flexibility, differentiated learning, and the integration of the Pancasila Student Profile. This study aims to analyze the challenges ISMUBA teachers face in designing and implementing teaching modules, examine how their understanding of curriculum principles influences classroom practices, and identify the strategies and professional support needed for effective implementation. This study employed a descriptive qualitative approach involving three ISMUBA teachers at SMP Muhammadiyah 1 Gamping. Data were collected through in-depth interviews, classroom observations, and document analysis. The data were analyzed using an interactive process consisting of data reduction, data display, and conclusion drawing, while validity was ensured through triangulation of sources and techniques. The findings indicate that teaching modules are perceived as more flexible and comprehensive than the 2013 Curriculum lesson plans, as they cover multiple learning sessions, integrate character development, and support differentiated learning. However, this flexibility also presents challenges, including the complexity of module preparation, limited teacher understanding, and relatively uniform evaluation practices. The study concludes that the successful implementation of teaching modules depends not only on curriculum design but also on teachers' pedagogical readiness, clear operational guidelines, and sustained professional and digital learning support.